Gandhi - Akinyemi, Rowena (Oxford ; New York : Oxford University Press, 2010)
Recounts the life of the Indian leader who helped gain independence for his country through passive resistance and non-violence. Includes activities.
Young Adult
Young Adult
Keywords: English language -- Textbooks for foreign speakers; Readers (Adult); Reading comprehension -- Problems, exercises, etc; English as a second language; Reading comprehension -- Problems, exercises, etc; Reading materials